THE INFLUENCE OF DHIKR AND PRAYER ON MENTAL HEALTH IN ADOLESCENTS AT THE SUBUL EL SALAM ISLAMIC BOARDING SCHOOL, INDONESIA: A NON-EQUIVALENT CONTROL GROUP DESIGN - Sarah Haya Fitria; Lastri Mei Winarni; Nurry Ayuningtyas Kusumastuti (Journal of Community Mental Health and Public Policy, 2026)
Background: Many problems that teenagers face today, such as social interaction, academic pressure, and searching for identity, can lead to mental health issues like stress, anxiety, and depression. Religion can help teenagers feel calm, clear their minds, and manage their behavior well, one of which is through activities like dhikr and prayer. Purpose: To determine "The Effect of Dhikr and Prayer on Mental Health in Teenagers at the Subul El Salam Islamic Boarding School, Tangerang Regency". Method: Using a Quasi-experimental with a Non-Equivalent Control Group Design design. The population & sample in this study were 40 teenagers. Sampling technique used total sampling. The instruments and measuring were questionnaires tools Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) scale and observation sheets with intervention media in the form of a dhikr and prayer guidebook "Laa Tahzan Wa Laa Takhof". The analysis technique used univariate and bivariate analysis with the Mann-Whitney test. Results: The Mann Whitney test results (P value = 0.001, so H1 is accepted) because the P value <0.05 it can be concluded that there is a significant influence between the application of dhikr and prayer on mental health in adolescents. Conclusion: It appears that the application of dhikr and prayer is effective in improving mental health in adolescents. Asbtrak Latar Belakang: Banyak masalah yang sering dihadapi remaja sekarang, seperti pergaulan sosial, tekanan belajar, dan mencari identitas diri, yang bisa menyebabkan gangguan kesehatan mental seperti stres, kecemasan, dan depresi. Agama bisa membantu remaja merasa tenang, tenang pikiran, dan mengendalikan perilaku dengan baik, salah satunya melalui kegiatan dzikir dan berdoa. Tujuan: Untuk mengetahui “Pengaruh Dzikir Dan Doa Terhadap Kesehatan Mental pada Remaja di Pondok Pesantren Subul El Salam Kabupaten Tangerang”. Metode: Quasi eksperimental dengan desain Non-Equivalent Kontrol Group Design. Populasi & sampel pada penelitian ini adalah remaja sebanyak 40 responden. Teknik pengambilan sampel ini menggunakan total sampling. Instrumen dan alat ukur berupa kuesioner skala Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) dan lembar observasi, media intervensi berupa buku panduan dzikir dan doa “Laa Tahzan Wa Laa Takhof”. Teknik analisis menggunakan analisa univariat dan bivariat dengan uji mann whitney. Hasil: hasil uji Mann- Whitney didapatkan nilai (P value = 0.001 maka H1 diterima) karena nilai P value <0,05 artinya karena nilai P value <0,05 maka dapat disimpulkan bahwa terdapat pengaruh yang signifikan antara penerapan dzikir dan doa terhadap kesehatan mental pada remaja. Kesimpulan: Terlihat penerapan dzikir dan doa efektif dalam meningkatkan kesehatan mental pada remaja.